Synthesis and biological evaluation of N6 derivatives of 8-azapurine as novel antiplatelet agents. Issue 8 (13th July 2021) - Zhao, Zhichang; Wang, Yeming; Tian, Nana; Yan, Hong; Wang, Juan
Abstract : Two series of novel N 6 derivatives of 8-azapurine I and II were designed as antiplatelet agents. Abstract : Two series of novel N 6 derivatives of 8-azapurine I and II were designed as antiplatelet agents. Series I and II were N 6 amino derivatives and N 6 hydrazone derivatives of 8-azapurine, respectively. The compounds were synthesized in acceptable yields via conventional procedures, including nucleophilic substitution, diazotization, and amination or hydrazonation with amino alcohol and 4, 6-dichloropyrimidine as starting materials. To assess the ability of the synthesized compounds as antiplatelet agents, the ADP-induced platelet aggregation assay of Born was performed both in vitro and in vivo using ticagrelor as a reference control substance. The analysis of the structure–activity relationship and molecular docking were also discussed in detail. The results demonstrated that series I and II compounds exhibited antiplatelet activity in vitro and IIh was the most active compound (IC50 = 0.20 μM) among the target compounds, being almost 4-fold better than ticagrelor (IC50 = 0.74 μM). For a preliminary assessment of the safety profile, a bleeding test (mouse tail) and a single-dose toxicity test were conducted. The use of compound IIh resulted in a shorter bleeding time, less blood loss and lower acute toxicity compared to ticagrelor. In addition, a molecular docking study was performed to investigate the binding capacity and binding mode between IIh and P2Y12 .